5'-ribonucleotides production using 5'-phosphodiesterase from spent malt roots - Alves, Edson Marcelino [UNESP]; De Souza, Joyce Faria [UNESP]; Macieja, Szymon [UNESP]; De Oliva Neto, Pedro [UNESP] (FapUNIFESP (SciELO), 2021)
5'-ribonucleotides are high value-added molecules widely used in the food and pharmaceutical industries because of their bioactive properties. The present work aims to produce a composition of 5’-ribonucleotides using spent brewer’s yeast as cheap source of RNA, and barley malt rootlets as cheap source of 5'-phosphodiesterase (5'-PDE). This is a very promising and innovative strategy because both spent yeast and malt rootles are residues of the brewing process and are closely linked in a cycle that until now is not yet commercially exploited due to lack of studies. Our results showed that extraction of 5’-PDE was mainly influenced by the fineness of the rootlets and amount of extraction solvent (water). The main molecules formed during RNA hydrolysis were 5’-ribonucleotides, which represented 85.86% of the total hydrolyzed molecules. Finally, the results of the proposed approach can generate a new perspective for the brewing industry regarding the management of its wastes, generating from them products of high added value and with a wide range of applications.
Produção de 5'-ribonucleotídeos utilizando 5'-fosfodiesterase da radícula de malte cervejeiro
Keywords: Barley malt rootlets; Bioprocess optimization; Brewing industry wastes; Enzyme kinetics; RNA hydrolysis; Spent brewer’s yeast